An Illustrated Guide to Pediatric Urology - Al-Salem, Ahmed H. (Springer International Publishing : Imprint: Springer, 2017)
This book is vital for physicians caring for young patients with urological conditions, as a quick reference book that is easy to read and well-illustrated. An Illustrated Guide to Pediatric Urology is useful to general surgeons, pediatricians, pediatric surgeons, fellows, residents, general physicians and family physicians, medical students and nurses.
Keywords: Medicine.; Pediatric surgery.; Urology.; elektronické knihy; electronic books